Feasibility of a best–worst scaling exercise to set priorities for autism research. (8th June 2022) - Davis, Scott A.; Howard, Kirsten; Ellis, Alan R.; Jonas, Daniel E.; Carey, Timothy S.; Morrissey, Joseph P.; Thomas, Kathleen C.
Abstract: Background: The preferences of autism stakeholders regarding the top priorities for future autism research are largely unknown. Objective: This study had two objectives: First, to examine what autism stakeholders think new research investments should be and the attributes of investment that they consider important, and second, to explore the feasibility, acceptability and outcomes of two prioritization exercises among autism stakeholders regarding their priorities for future research in autism. Design: This was  a prospective stakeholder‐engaged iterative study consisting of best–worst scaling (BWS) and direct prioritization exercise. Setting and Participants: A national snowball sample of 219 stakeholders was included: adults with autism, caregivers, service providers and researchers. Main Outcome Measures: The main outcomes measures were attributes that participants value in future research investments, and priority research investments for future research. Results: Two hundred and nineteen participants completed the exercises, of whom 11% were adults with autism, 58% were parents/family members, 37% were service providers and 21% were researchers. Among stakeholders, the BWS exercises were easier to understand than the direct prioritization, less frequently skipped and yielded more consistent results. The proportion of children with autism affected by the research was the most important attribute for all types of stakeholders. The top three priorities among future research investments were (1) evidence on which child, family and intervention characteristics lead to the best/worst outcomes; (2) evidence on how changes in one area of a child's life are related to changes in other areas; and (3) evidence on dietary interventions. Priorities were similar for all stakeholder types. Conclusions: The values and priorities examined here provide a road map for investigators and funders to pursue autism research that matters to stakeholders. Patient or Public Contribution: Stakeholders completed a BWS and direct prioritization exercise to inform us about their priorities for future autism research.